THE ROLE OF THE HUMANITARIAN ACTION INTERNATIONAL COMMITTEE FOR THE RED CROSS (ICRC) IN THE 2011 LIBYA REVOLUTION - Setyorini, Fitri Adi (Universitas Muhammadiyah Yogyakarta, 2021)
This study discusses the International Committee for the Red Cross (ICRC) role in protecting and assisting victims of the Libyan revolution in 2011. The purpose of this study is to explore more about the role of the International Committee for the Red Cross (ICRC) in protecting and assisting victims of war as one step on a humanitarian mission. The author used the non-government organizations (NGOs) and humanitarian action concepts. The author's research method to analyze this study was a descriptive method through a literature review. Based on research done, the author found that the revolution in Libya in 2011 was one of the effects of the Arab Spring in the Middle East region. The author also found that the ICRC carried out its humanitarian missions by providing food, water, medical supplies, medical equipment, and clothing.